2017
DOI: 10.1111/and.12840
|View full text |Cite
|
Sign up to set email alerts
|

Sperm telomere length in motile sperm selection techniques: A qFISH approach

Abstract: Several studies have associated telomere shortening with alterations in reproductive function. The objective of the present study was to determine telomere length (TL) in spermatozoa selected by either density-gradient centrifugation (DGC) or swim-up. The analysis of TL was performed using quantitative fluorescent in situ hybridisation (qFISH) using PNA probes in combination with a chromatin decompaction protocol in sperm cells. Results of TL were 24.64 ± 5.00 Kb and 24.95 ± 4.60 Kb before and after DGC, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 46 publications
2
28
1
Order By: Relevance
“…21 In another study, it was demonstrated that spermatozoon with shorter STL was associated with lower natural pregnancy rates compared with couples who did achieve pregnancy naturally with longer STL. 18 Herein, a trend was observed in which 14,16,18,21 Studies investigating the association between STL and sperm quality have shown a positive correlation with total sperm count and STL. 14,21 In other studies using normozoospermic samples, STL was found to be positively linked to sperm progressive motility/ vitality and negatively linked to sperm DNA fragmentation 15, but no association was detected with male age, sexual abstinence, total sperm count, concentration and morphology.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…21 In another study, it was demonstrated that spermatozoon with shorter STL was associated with lower natural pregnancy rates compared with couples who did achieve pregnancy naturally with longer STL. 18 Herein, a trend was observed in which 14,16,18,21 Studies investigating the association between STL and sperm quality have shown a positive correlation with total sperm count and STL. 14,21 In other studies using normozoospermic samples, STL was found to be positively linked to sperm progressive motility/ vitality and negatively linked to sperm DNA fragmentation 15, but no association was detected with male age, sexual abstinence, total sperm count, concentration and morphology.…”
Section: Discussionmentioning
confidence: 89%
“…16,17 Furthermore, Lafuente et al demonstrated that STL in infertile men was negatively correlated with sperm concentration and progressive motility. 18 An increasing number of studies have found that STL may play a role in reproduction as a molecular marker of sperm quality.…”
Section: Introductionmentioning
confidence: 99%
“…In total, 15 of the positively associated studies detected a sperm TL (STL) association (68-70,72,74-84), while 3 studies detected an LTL association (73,85,86), and one study detected both STL and LTL (71). In several studies, shorter STL was reported in association to infertility (72,76,78,80) while Vecoli et al reported an increase in STL in areas of high environmental exposure (77). Although Turner and Hartshorne found an association between female fertility and STL, they did not find a significant association for male fertility (39).…”
Section: Telomere Length and Male Infertilitymentioning
confidence: 99%
“…Although telomere length is partially determined genetically and by paternal age, it is also influenced by internal and external environmental factors such as obesity, infection, oxidative stress, smoking, psychological and lifestyle stress, environmental factors and diet (Thilagavathi et al., ). However, currently, analysing sperm telomere length is not a part of standard clinical practice due to some conflicting data surrounding its relationship with sperm DNA fragmentation, sperm parameters and reproductive outcomes (Cariati et al., ; Lafuente et al., ; Rocca et al., ; Turner & Hartshorne, ; WHO, ). Thus, the validity of telomere length as a diagnostic tool of infertility and OS has yet to be confirmed.…”
Section: Introductionmentioning
confidence: 99%